IMPROVING THE STUDENTS’ VOCABULARY MASTERY THROUGH RIDDLE GAME TECHNIQUE AT THE EIGHT GRADE OF JUNIOR HIGH SCHOOL STUDENTS OF SMP SWASTA R.A KARTINI TEBING TINGGI - APRILIANDRI TANJUNG, LUSY (Faculty of Tarbiyah nad Teacher Training, 2021)
This research was aimed to improve the students’ vocabulary mastery by using riddle games. The subjects of this study were 25 students at eight grade in smp swasta R.A Kartini Tebing Tinggi. This research was conducted by using classroom action research that consist of 2 cycles. The technique of analyzing data for quantitative data was the students’ score of test. While for qualitative data, the researcher used observation and interview. The result of this research showed that the mean of the students score was 51,6 in which there were 4 from 25 students (16%) who passed the minimum criteria of mastery learnings (KKM). In the post test I, there were 10 from 25 students (40%) who improved and the score mean was 63,6. Meanwhile, in the post test II, the mean score was 84,8. There were 23 students (92%) passed the minimum criteria of mastery learnings (KKM). It is indicated that riddle game could improve the students’ vocabulary. This result is strength by the observation and the interview result that students were more active in the class and enjoy the learning process Keywords: Vocabulary Mastery, Using Riddle Game